2021
DOI: 10.3389/fnagi.2021.676899
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Regional Homogeneity in the Mild and Moderate Stages of Parkinson’s Disease

Abstract: Objectives: This study aimed to investigate alterations in regional homogeneity (ReHo) in early Parkinson’s disease (PD) at different Hoehn and Yahr (HY) stages and to demonstrate the relationships between altered brain regions and clinical scale scores.Methods: We recruited 75 PD patients, including 43 with mild PD (PD-mild; HY stage: 1.0–1.5) and 32 with moderate PD (PD-moderate; HY stage: 2.0–2.5). We also recruited 37 age- and sex-matched healthy subjects as healthy controls (HC). All subjects underwent ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…Functional connectivity changes in some brain networks may not be apparent at this time. In a previous study, we investigated different patterns of altered brain activity in PD at different stages of the disease, and found that the higher the grade, the more extensive the involvement of the brain (Li et al, 2021). Thirdly, our study is a cross-sectional study.…”
Section: Increased Functional Connectivity Within the Sensorimotor Ne...mentioning
confidence: 80%
“…Functional connectivity changes in some brain networks may not be apparent at this time. In a previous study, we investigated different patterns of altered brain activity in PD at different stages of the disease, and found that the higher the grade, the more extensive the involvement of the brain (Li et al, 2021). Thirdly, our study is a cross-sectional study.…”
Section: Increased Functional Connectivity Within the Sensorimotor Ne...mentioning
confidence: 80%
“…The key component of PD pathogenesis is a degeneration of DAergic neurons of the SNc, resulting in the deafferentation of the striatum (7,47). The onset of cellular neurodegenerative mechanisms underlying PD precedes the appearance of the disease symptoms by multiple years (14,46,48): estimations date the initial presymptomatic phase 5 to 30 years prior to the clinical manifestation (6). Motor symptoms first appear in patients after the degeneration of 50-60% of DAergic neurons and 70-80% dopamine depletion in the striatum (22,(44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, most of the classic literature based on animal experiments -monkey and rodent models -and human studies reflect late, chronic, dopamine-depleted states when compensatory mechanisms are already in place in most related neural network functions (2,11,12). In the past decades, however, early stages of the disease have received increasing focus (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…PD patients have been reported to have structural or functional changes in the Rolandic operculum (ROL) 42,43 . In early PD, reduced ReHo values in the ROL are most likely connected to swallowing and speech disorders 44 . In patients with amyotrophic lateral sclerosis, gray matter atrophy in the ROL is associated with movement disorders or tonic contractions of the perioral muscles, which could induce swallowing dysfunction or dysarthria 45 .…”
Section: Discussionmentioning
confidence: 99%